Assessing the cyber-security of the IEC 60870-5-104 protocol in SCADA system - Qassim Q.S.; Jamil N.; Z'aba M.R.; Kamarulzaman W.A.W. (Inderscience Publishers, 2023)
Computer crime; Crime; Network security; SCADA systems; Critical infrastructure systems; Electrical power system; Industrial controls; Industrial processs; International standards; Malicious activities; Security vulnerabilities; Supervisory control and dataacquisition systems (SCADA); Electric power system control